PERILAKU KONSUMEN DALAM PEMBELIAN SAYURAN DI PASAR TRADISIONAL KOTA METRO - Inggitina Sasmaya; Yaktiworo Indriani; Dame Trully Gultom (Lampung University, 2019)
The purpose of this study is to determine the consumer characteristics, consumer attitudes, the stages of decision making, and factors that influence vegetable buying at traditional market in Metro City. This study used a survey method. The research sample of 60 people was selected through accidental sampling. The research data were analyzed by quantitative descriptive, Multi-Attribute Fishbein, and Seemingly Unrelated Regression Analysis. The results showed that most of the consumers were Javanese aged 25-35 years old with the marital status of consumers who were wives whose household members were 3-4 people. Vegetable consumers were mostly housewives who graduated from high school and had income of below IDR3,000,000/month. The highest consumer attitude towards vegetables was given to spinach. The appetites for each type of vegetable influenced the amount they bought. In addition, the purchase of eggplant was influenced by its price, spinach, cassava leaves and eggs prices, and appetite towards spinach; of long beans was influenced by its price and tempeh price, number of household members, and appetite for spinach; of spinach was influenced by its price, long beans and tempeh prices, and household income; of water spinach was influenced by appetite for spinach; while of cassava leaves was influenced by its price and tempeh price, household income, and number of household members.Key words: appetite, attitude, buying, consumer behavior, vegetables.